PESAN MORAL DALAM FILM YOWIS BEN - Andy Wicaksono, Galuh; Qorib, Fathul (Jurnal Komunikasi Nusantara, 2019)
The number of movies made in Indonesia there are several films that give a good moral message in it. Through the movie "Yowis Ben" the director tried to make something new and different from the comedy genre films on previous comedy films. The purpose of this research is to know and understand the moral messages contained in the movie Yowis Ben. In this study used qualitative research method by using the research object of the Film Yowes Ben. While the data analysis technique uses the semiotic analysis of Charles Sander Pierce which is based on logic, with reasoning through the signs. The Model that shows the three main elements of the marking forming is representament, object and Interpretant. The results of this research show that the YOWIS BEN film has a moral message in various sides of life through signs that are munncul both visual and verbal in their respective stories. There is a moral message related to Bayu's life. It can therefore be concluded that the figures and the talks that exist in each scene are a representation of the moral message.